Peran Manajemen Waktu dan Kepemimpinan Guru Pesantren dalam Pelaksanaan Tugas Pendidikan Perspektif Manajemen Syariah - Nabiila Irawan; Tri Aryani Arumaniar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Indonesia hosts over 42,000 pesantren, yet fewer than one-third operate under systematic time management. Meanwhile, studies conducted in the 2021–2025 period have largely targeted formal schools and rarely examined female tahfidz boarding schools. Addressing this gap, the present study investigates how time management and teacher leadership at Pesantren Tahfidhul Qur'an Imam Syafii Putri Brebes influence educational task execution from a sharia management perspective. A descriptive qualitative approach was employed, drawing data from 15 informants—comprising the pesantren leader, ustadzah, administrators, and students—through in-depth interviews, participatory observation, and document review. Data analysis followed the Miles, Huberman, and Saldaña interactive model. Three key findings emerged: first, a structured 24-hour time management system—spanning from the tahajud schedule to nightly evaluations—demonstrably supports student focus and discipline. Second, teacher leadership anchored in exemplary conduct (uswah hasanah), deliberation (syura), and spiritual motivation fosters intrinsic tahfidz enthusiasm among students. Third, these practices collectively reflect the sharia principles of shiddiq, amanah, fathanah, and tabligh, constituting an integrative sharia-based pesantren management model. This model holds potential for adoption by other pesantren facing similar challenges.